The Role of the Indonesian National Armed Forces (TNI) in Supporting Regional Development Acceleration in Papua - Jorry S Koloay; Antonius W; G. Luky (Publikasi Indonesia, 2024)
The conflict in Papua has evolved into an increasingly complex situation, with the separatist movement led by the Free Papua Organization (OPM) seeking to break away from Indonesia. This study examines the role of the Indonesian National Armed Forces (TNI) in supporting the acceleration of regional development in Papua amidst the ongoing conflict involving the Free Papua Organization (OPM). The primary objective is to analyze the TNI’s use of a